Probing intramolecular vibronic coupling through vibronic-state imaging - Fan-Fang Kong (Nature Portfolio, 2021)
Vibronic coupling is a key feature of molecular electronic transitions, but its visualization in real space is an experimental challenge. Here the authors, using scanning tunneling microscopy induced luminescence, resolve the effect of vibronic coupling with different modes on the electron distributions in real space in a single pentacene molecule.